2014
DOI: 10.1179/1607845414y.0000000197
|View full text |Cite
|
Sign up to set email alerts
|

Impact of educational programme regarding chelation therapy on the quality of life for B-thalassemia major children

Abstract: Objectives Thalassemia is the most common genetic disorder in Egypt, with an estimated carrier rate of 9-10%. It is a genetic blood disorder which can be fatal if proper chelation is not received. The introduction of chelating agents capable of removing excessive iron from the body has dramatically increased life expectancy and improved the overall quality of life. The aim of this study was to assess the impact of educational programmes regarding chelation therapy on the quality of life of thalassemic children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
3
14
0
1
Order By: Relevance
“…A recent study revealed that higher social functioning scores and educatory intervention have been reported in association with higher educational levels of TM patients and resulted in greater effectiveness of chelation therapy and quality of life of TM patients. 24 In this study, we observed that many patients had features of severe BT, such as severe anemia, growth retardation, hepatosplenomegaly, bone marrow expansion, and bone deformities, as originally described by Cooley. 25 In our study group, being underweight and stunted were significantly higher in those older than five years who had been in their country during the war, which may be an indicator of the severity of the conditions.…”
Section: Refugee Children In Turkeysupporting
confidence: 65%
See 1 more Smart Citation
“…A recent study revealed that higher social functioning scores and educatory intervention have been reported in association with higher educational levels of TM patients and resulted in greater effectiveness of chelation therapy and quality of life of TM patients. 24 In this study, we observed that many patients had features of severe BT, such as severe anemia, growth retardation, hepatosplenomegaly, bone marrow expansion, and bone deformities, as originally described by Cooley. 25 In our study group, being underweight and stunted were significantly higher in those older than five years who had been in their country during the war, which may be an indicator of the severity of the conditions.…”
Section: Refugee Children In Turkeysupporting
confidence: 65%
“…We observed that children are mostly fluent in Turkish and act as a translator between their families and the medical staff. A recent study revealed that higher social functioning scores and educatory intervention have been reported in association with higher educational levels of TM patients and resulted in greater effectiveness of chelation therapy and quality of life of TM patients …”
Section: Discussionmentioning
confidence: 99%
“…The final form of the Thalassemia Major Knowledge Questionnaire (the modified form) composed of 17 items and the responses were modified to be scored (2) for the complete correct answer, (1) for the incomplete answer, and (0) for wrong answer or don't know response. Knowledge score was considered weak, acceptable and good when total score were less than 13, between 13 to 24 and more than 24 respectively (Shareef & Obaid 2015).…”
Section: Scoring Systemmentioning
confidence: 99%
“…Bütün bunlar eğitim ve danışmanlığı içermektedir. Beta-talasemili çocuklara verilen eğitim yaşam kalitelerini arttırmıştır (30) . Tanı alma yaşı, transfüzyon sıklığı, Hb ve ferritin değerleri, endokrin, işitme, kalp, ve ağız diş sağlığı sorunu olması ile yaşam kalitesi puanları arasında anlamlı bir fark saptanmamıştır (p>0,05).…”
Section: Araştırmanın Etiğiunclassified